UV-light promoted C–H bond activation of benzene and fluorobenzenes by an iridium(i) pincer complex. Issue 26 (17th March 2017) - Hauser, Simone A.; Emerson-King, Jack; Habershon, Scott; Chaplin, Adrian B.
Abstract : UV irradiation of [Ir(2, 6-(P t Bu2 CH2 )2 C6 H3 )(CO)] generates the transient and reactive 14 VE Ir(i ) fragment Ir(2, 6-(P t Bu2 CH2 )2 C6 H3 ), which subsequently undergoes C–H bond activation of benzene and fluorobenzenes. Abstract : Iridium(i ) carbonyl complex [Ir(2, 6-(P t Bu2 CH2 )2 C6 H3 )(CO)] undergoes reversible C–H bond activation of benzene and a series of fluorobenzenes on UV irradiation. Exclusive ortho -selectivity is observed in reactions of fluorobenzene and 1, 2-difluorobenzene.